Education in North East India experience and challenge - De Utpal Kumar; Lyndem Biloris (New Delhi Concept Publishing, 2004)
The papers in this volume, presented at a seminar organized by North East India Council for Social science Research, attempt to explore the status of education in Northeast India & its role in the development of the region. They address a range of issues
Keywords: Education; North East India